CSC415: Fundamentals of Computer Problem Solving / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (2022)
This course is an introduction to problem solving using computers. It emphasizes various aspects of problem solving, mainly consisting of the problem domain, phases of problem solving and basic techniques in designing a solution. The approach to problem solving is via structured programming. At this stage, the emphasis will be on computer problem solving rather than syntactical aspects of the chosen programming language.